ANALISIS KEBUTUHAN E-LKPD PEMBELAJARAN IPS MATERI DAERAHKU KEBANGGAANKU DI KELAS V SEKOLAH DASAR - Awalia Zahra, Lisnie; Merliana, Anggit; Mohamad Setiadi, Pidi (Universitas Negeri Medan, 2025)
This study analyzes the need for the development of an electronic-based Interactive Student Worksheet (E-LKPD) in Social Studies (IPS) learning in grade V. Focusing on the initial analysis stage using the ADDIE development model, this study involved interviews with teachers to identify student needs, curriculum analysis, materials, and learning techniques. The results show that IPS learning is often monotonous due to the less interesting textbook-based approach and minimal use of technology. Teachers and students need E-LKPD as a more interactive teaching material to increase enthusiasm for learning, relevant to the Independent Curriculum which supports technology-based learning. The research method uses a research and development (R&D) approach, focusing on analyzing students' needs and learning styles. The use of E-LKPD is expected to overcome existing obstacles, provide a more creative and enjoyable learning experience, and increase student involvement in IPS learning.